Estrategias de enseñanza docente en el rendimiento académico de los niños/as con necesidades educativas especiales en la educación básica regular de las I.E del nivel de inicial en el distrito de Rioja - Guerra Ganoza, Llayaneth Ketty (2012)
This research entitled "teacher teaching strategies in the academic performance of children with special educational needs in regular primary education level educational institutions in the district early Rioja, 201 0," aims to determine the influence of teachers teaching strategies in the academic performance of children with special educational needs supported with the theoretical framework of the Ministry of Education, particularly the National Special Basic Education. We worked with a sample population of seven teachers and seven children (as) with special educational needs in the district of Rioja. The techniques used for information were observing teachers and children (as) and parent interviews. Accepting the alternative hypothesis which states that teachers teaching strategies do not favor the development of learning achievement of children with special educational needs in regular primary education level educational institutions in the district early Rioja, 201 O . Once the research process we carne to the following conclusion: that the academic performance of children with special educational needs in the Basic Education of the lnitial Level Educational lnstitutions are in the top level, ie in the area of mathematics have an average of 0.79, in communication, 0.79; social staff, 0.76 and science and environment, 0.82.Las teaching strategies. and the development of learning achievements (academic) of children with special educational needs in the Basic Education Educational lnstitutions of the initiallevel, we have obtained the Spearman correlation coefficient (). lndicating that academic achievement is influenced by 47.27% for teachers teaching strategies, this means that teachers teaching strategies are not favoring the development of learning achievement.